2022
DOI: 10.1007/s11696-022-02170-8
|View full text |Cite
|
Sign up to set email alerts
|

In silico approach for the development of novel antiviral compounds based on SARS-COV-2 protease inhibition

Abstract: The COVID-19 pandemic emerged in 2019, bringing with it the need for greater stores of effective antiviral drugs. This paper deals with the conformation-independent, QSAR model, developed by employing the Monte Carlo optimization method, as well as molecular graphs and the SMILES notation-based descriptors for the purpose of modeling the SARS-CoV-3CLpro enzyme inhibition. The main purpose was developing a reproducible model involving easy interpretation, utilized for a quick prediction of the inhibitory activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Ničkčović et al also extracted 84 heterocyclic molecules in the Binding database with the definitive inhibitory activity (IC 50 ) against 3CLpro of SARS-CoV to construct the Monte Carlo-based QSAR model [ 66 ]. It should be noted that the SMILES notation and molecular graph-based descriptors were used for model development.…”
Section: Qsar Models Of Sars-cov-2 Main Protease Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ničkčović et al also extracted 84 heterocyclic molecules in the Binding database with the definitive inhibitory activity (IC 50 ) against 3CLpro of SARS-CoV to construct the Monte Carlo-based QSAR model [ 66 ]. It should be noted that the SMILES notation and molecular graph-based descriptors were used for model development.…”
Section: Qsar Models Of Sars-cov-2 Main Protease Inhibitorsmentioning
confidence: 99%
“…Similarly, molecular docking was also used by Ničkčović et al to validate the inhibitory activity of the five newly designed molecules (from QSAR-aided design, see Table S3 ) on the 3CLpro of SARS-CoV. The results showed that the new molecule with the highest predictive activity in the QSAR also possessed the best docking score [ 66 ].…”
Section: Molecular Docking Molecular Dynamics Drug-like Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This method involves the mathematical modeling of the relationship between physicochemical properties or molecular descriptors of compounds and their biological activities. Studies have been carried out using QSAR methods to develop phosphorus-based drugs, which have good inhibitory activity against SARS-CoV-2 proteins and their non-synonymous variants [66][67][68]. A QSAR study based on the simplified molecular-input line-entry system (SMILES) strings of 32 bicycloproline derivatives has also been applied in the discovery of COVID-19 therapeutics, with the strings applied in calculating 0D, 1D, and 2D molecular descriptors [69].…”
Section: Quantitative Structure-activity Relationships (Qsar) Mappingmentioning
confidence: 99%